Budget Control Model to Improve the Perception of Public Value, From the Perspective of Peruvian Students - Rimarachin Chupillon, Orlando (2025)
The The objective was to propose a budget control model to improve the perception of public value, from the perspective of the Peruvian student. Applied research, non-experimental, quantitative, cross-sectional, descriptive and propositional design. The population and sample were 70 students. The technique was the survey and the instrument the questionnaire. The results show that there are deficiencies in the qualification of the teaching work 44.3%, the risks are not correctly identified 44.3%, there is a deficiency of formats to control the delivery of teaching materials 37.1%, regarding satisfaction with the public value there is no economic mi support 18.6%, 10% consider that the achievement of cultural results is not correctly raised. It was concluded that the budget execution control proposal improves the satisfaction of the public value according to the judgment of experts who determined it favorable and is applicable, also, the design of the proposal includes the strengthening of human resources management, risk management, inter-institutional articulation among others that will achieve student well-being.